การออกแบบระบบการจัดการคลังสินค้าในส่วนกิจกรรมครอสส์-ด็อกกิ้ง - อุดมทัศนีย์ อินทรโชติ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The objective of this research is to design and develop the system for the cross-docking warehouse management. In the cross-docking warehouse, products arrive in bulk and are immediately broken down and mixed for customer shipments without storage activity. However, minimum order quantity causes some inventory in storage area. In this research, the just-in-time concept was applied. So, there is no sales forecast but considering only actual demand and planning to receive required materials at the right time and place. This is to reduce cost and time products remain at the warehouse, thus improving customer service levels. The research phases included requirements specification, system analysis, system design and software development. The system was designed for processing the customer orders, planning inventory requirements, issuing the purchase orders, receiving and transferring the receipts of purchased materials, maintaining accurate records of inventories on hand and on order and controlling over materials in stores. There are 3 major modules in this system : material management support, warehouse activity control and inventory control. The proposed system was tested for 2 weeks and it helped the warehouse making decisions and setting up suitable work plans. Cross-docking concept also reduced inventory levels and improved customer service levels. Moreover, this research can lead to further development of new warehouse management systems and softwares.